Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1021/jf035213x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Chalcones and New Caffeic Acid Esters fromZuccagnia punctataActing against Soybean Infecting Fungi

Abstract: The crude methanolic extract of Zuccagnia punctata was active toward the fungal pathogens of soybean Phomopsis longicolla and Colletotrichum truncatum. Assay guided fractionation led to the isolation of two chalcones, one flavanone and a new caffeoyl ester derivative as the compounds responsible for the antifungal activity. Another new caffeoyl ester derivative was isolated from the antifungal chloroform extract but proved to be inactive against the soybean infecting fungi up to 50 microg/mL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
8

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 14 publications
4
92
0
8
Order By: Relevance
“…Data collection: APEX2 (Bruker, 2010); cell refinement: SAINT (Bruker, 2010); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEP-3 (Farrugia, 1997) and Mercury (Macrae et al, 2008); software used to prepare material for publication: SHELXL97 and PLATON (Spek, 2009 (Lin et al, 2002), anticancer (Modzelewska et al, 2006) and antifungal agents (Svetaz et al, 2004). The crystal structures of some chalcones such as (2E)-1-(2,6-Dichloro-3-fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Betz et al, 2012) have been reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection: APEX2 (Bruker, 2010); cell refinement: SAINT (Bruker, 2010); data reduction: SAINT; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: ORTEP-3 (Farrugia, 1997) and Mercury (Macrae et al, 2008); software used to prepare material for publication: SHELXL97 and PLATON (Spek, 2009 (Lin et al, 2002), anticancer (Modzelewska et al, 2006) and antifungal agents (Svetaz et al, 2004). The crystal structures of some chalcones such as (2E)-1-(2,6-Dichloro-3-fluorophenyl)-3-(4-fluorophenyl)prop-2-en-1-one (Betz et al, 2012) have been reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…For pharmaceutical background to chalcones, see : Lin et al (2002); Modzelewska et al (2006); Svetaz et al (2004). For related structures, see: Betz et al (2012).…”
Section: Related Literaturementioning
confidence: 99%
“…Two natural chalcones isolated from the leaves of Myrica serrata, 2',4'-dihydroxy-3',5'-dimethyl-6'-methoxychalcone and stercurensin, showed a strong inhibitory effect on the growth of Cladosporium cucumerinum, a fungus that typically affects cucumber (Gafner et al, 1996). The 2',4'-dihydroxy-3'-methoxychalcone and the 2',4'-dihydroxychalcone isolated from Zuccagnia punctata (Fabaceae) were found to be active against the pathogenic fungi Phomopsis longicolla, Alternaria alternate, Fusarium equiseti, F. graminearum, F. verticillioides, Colletotrichum truncatum and Sclerotium bataticola, and if used at the concentration of 6.25 µg/mL completely inhibited the growth of P. longicolla and C. truncatum (Svetaz et al, 2004;Jimenez et al, 2014). As well, five chalcones isolated from Artocarpus nobilis (Moraceae) were found to have antifungal activity against Cladosporium cladosporioides, which typically affects wheat, or against Aspergillus niger, which causes black mould in certain fruits and vegetables (Jayasinghe et al, 2004;Thirunarayanan and Vanangamudi, 2014).…”
Section: Fungicidesmentioning
confidence: 99%
“…Chalcones are compounds highly toxic for many phytoparasitic nematodes, even more than some commercial nematicidal as in the (Rao et al 1994) Nematicide (González and Estévez-Braun, 1998) Phytotoxic (Chen et al, 2004;Díaz-Tielas et al, 2013) 2',4'-dihydroxy-3'-methoxy-chalcone Fungicidal (Svetaz et al, 2004;Jimenez et al, 2014) 2´,3,4,4´-tetrahydroxy-3´-geranylchalcone…”
Section: Nematicides Insect Deterrents and Antifeedantsmentioning
confidence: 99%
“…Chal-cones (1, 3-diaryl-2-propen-1-ones), constituting an enone system between two aromatic rings are an important class of natural products which are considered as precursors for various flavonoids and exhibit interesting pharmacological activities (Stu et al, 1971). Chalcones, originating from natural and synthetic routes possess several biological activities, such as cytotoxic (Modzelewska et al, 2006) anti-malarial (Dominguez et al, 2005), antileishmanial (Boeck et al, 2006) anti-inflammatory (Yang et al, 2007), anti-HIV (Cheenpracha et al, 2006), antifungal (Svetaz et al, 2004) and as tyrosine kinase inhibitors (Neryr et al, 2004). Because of very high pharmacological interest, these molecules have attracted medicinal chemists to design and synthesize further large number of chalcones with different functional groups.…”
Section: Introductionmentioning
confidence: 99%